PENGARUH LATIHAN BENCH PRESS TERHADAP KEKUATAN OTOT LENGAN DAN BAHU TERHADAP PUKULAN PADA ATLIT TINJU PUTERA DENPAL BOXING CAMP PEKANBARU - Oqta Mesi; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem of this research are some shortcomings, especially in physical condition, muscle strength of arms and shoulders seen when they are practicing sedo boxing, samsak, and at the time of sparing. Can be seen at the time of athlete Dreal Patner a lot of punches in catapult boxing athletes do not have the weight of a punch that means that the opponent does not change the position but returns back punch. The type of this research is research with experimental treatment (Experimental), this research population is athlete son denpal boxing camp Pekanbaru, the sample in this research is the entire population of 6 people. The data retrieval technique can be from pre-test and post-test. The instrument performed in this research is an exspanding dynamometer test, which aims to measure the strength of arm and shoulder muscles. Variables that exist in this research is bench press exercise which is denoted by X as independent variable, while muscle strength of arm and shoulder is denoted by Y as dependent variable. After that, the data were processed with statistics, to test the normality by liliefors test with a significant level of 0.05. The hypothesis proposed is the influence of bench press exercises on the muscle strength of the arms and shoulders against the blow at the male boxing athletes booxing camp Pekanbaru. Based on T test analysis, the conclusion is obtained: Tcount of 2.78 and Ttable 2.015, means Tcount > T table. It can be concluded that Ho is rejected and HI accepted, this concludes that there is significant influence between bench press exercise on muscle strength of arm and shoulder at athlete of son boxing camp PekanbaruKeywords : Bench Press, Muscle Sleeve and Shoulder Strength